Potensi Narasi Visual Video Pertunjukan Wayang Dewa Ruci sebagai Media Pembelajaran Bahasa Jawa - Safira Rizky Rachmania Hadi; Irfansyah Irfansyah (Universitas Indraprasta PGRI, 2022)
The wayang story is one of the chapters or main material in Javanese language subjects which is considered difficult for high school students to learn. So that the results of student achievement at SMA N 2 Wonogiri on the material for wayang stories are the lowest among other materials in Javanese language subjects. The Javanese language teacher's effort to overcome this problem is to show a video of a shadow puppet show with Dewa Ruci's story to the students. The video has visual narrative elements that can convey information on wayang stories sequentially and effectively to students. The purpose of this study was to determine the potential of a video of a shadow puppet show that can be used as learning media for students to recognize and understand the Javanese language subjects. This research method uses a mixed-method (quantitative-qualitative). The results showed that learning material for wayang stories in Javanese language subjects through a video of a shadow puppet show with Dewa Ruci stories for high school students proved to be more effective to understand because it contained visual narrative elements. High school students can find out the characters, setting, plot, themes, and moral values and can rewrite Dewa Ruci's story into Javanese. As a result, through the storytelling of the dalang and the dialogue between the characters in the performances, the dalang becomes known and understood by students.